Syntactic Deviations and Semantic Oddities in Cody Fry’s Pictures of Mountains Album - Ana Maria Jati Aryani; Made Frida Yulia (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study identified the syntactic deviations and semantic oddities in the song lyrics of the Pictures of Mountains album by Cody Fry. The lyrics of the songs were pleasant to listen to. However, there were some intentional deviations, which could catch the listeners’ attention. In order to explore that phenomenon, this research employed qualitative content analysis to analyze the lyrics of eleven songs in the Pictures of Mountains album. One song out of twelve was not included as the object of this research due to the absence of lyrics in it. The analysis revealed that this album showed two types of syntactic deviations. Those were 44 instances of omission and 2 types of addition, which varied from parts of speech, clauses, and particles. Nevertheless, misordering and misformation, as other types of syntactic deviations, did not appear in the album. On the other hand, 10 occurrences paradox and an example pleonasm recognized as forms of semantic oddities in the album. Meanwhile, periphrasis and oxymoron were nonexistent in all the song lyrics of the mentioned album. The findings of this research contribute to linguistic study by pointing out how syntactic deviations and semantic oddities serve as intentional linguistic variations in song lyrics. Moreover, it offers new insights on the contributions of the songwriter’s works to the discussion about language and its creativity. Lastly, it serves as proof that linguistic phenomena vary across literary works, such that language can be modified to enhance the unique expression and emotional portrayal.